The execution premium : linking strategy to operations for competitive advantage - Kaplan, Robert S.; Norton, David P. (Boston, Mass. : Harvard Business Press, 2008)
The Execution Premium is a comprehensive and insightful field book for business leaders responsible for steering their organizations's long-term sucess.It is a great example of how to successfully execute strategy in the organization.
Includes bibliographical references and index.
rua 29/04/13
Loans
Keywords: Strategic planning; Business planning; Organizational effectiveness